The Effect of Palmitoylethanolamide (PEA) on Skeletal Muscle Hypertrophy, Strength, and Power in Response to Resistance Training in Healthy Active Adults: A Double-Blind Randomized Control Trial - Zoya Huschtscha; Jessica Silver; Michael Gerhardy; Charles S. Urwin; Nathan Kenney; Viet Hung Le; Jackson J. Fyfe; Simon A. Feros; Andrew C. Betik; Christopher S. Shaw; Luana C. Main; Gavin Abbott; et al. (SpringerOpen, 2024)
Abstract Background Palmitoylethanolamide (PEA) has analgesic/anti-inflammatory properties that may be a suitable alternative to over-the-counter (OTC) non-steroidal analgesics/anti-inflammatories. While OTC pain medications can impair strength training adaptations, the mechanism of action of PEA is distinct from these and it may not negatively affect skeletal muscle adaptations to strength training. Methods The primary aim of this study was to investigate the effects of daily PEA supplementation (350 mg Levagen + equivalent to 300 mg PEA) combined with 8-weeks of resistance training on lean body mass with secondary aims addressing strength, power, sleep, and wellbeing compared to placebo (PLA) in young, healthy, active adults. In a randomized, controlled, double-blinded trial, 52 untrained, recreationally active participants aged 18-35 y were allocated to either the PEA or PLA groups. Participants consumed either 2 × 175 mg Levagen + PEA or identically matched maltodextrin capsules during an 8-week period of whole-body resistance training. This trial assessed the pre- to post- changes in total and regional lean body mass, muscular strength (1-RM bench, isometric mid-thigh pull), muscular power [countermovement jump (CMJ), bench throw], pain associated with exercise training, sleep, and wellbeing compared with the PEA or PLA condition. Results 48 Participants were included in the final intention to treat (ITT) analysis and we also conducted per protocol (PP) analysis (n = 42). There were no significant between-group differences for total or regional lean muscle mass post-intervention. There was a significantly higher jump height (CMJ) at week 10 in the PEA group compared to the PLA (Adjusted mean difference [95% CI] p-value; ITT: − 2.94 cm [− 5.15, − 0.74] p = 0.010; PP: − 2.93 cm [− 5.31, − 0.55] p = 0.017). The PLA group had higher 1-RM bench press post-intervention compared with the PEA group (ITT: 2.24 kg [0.12, 4.37] p = 0.039; PP: 2.73 kg [0.40, 5.06] p = 0.023). No significant treatment effects were noted for any of the other outcomes. Conclusion PEA supplementation, when combined with 8 weeks of strength training, did not impair lean mass gains and it resulted in significantly higher dynamic lower-body power when compared with the PLA condition. Trial Registration: Australian New Zealand Clinical Trials Registry (ANZCTR: ACTRN12621001726842p).